Best practice promotion in Europe: A web-based tool for the dissemination of evidence-based demand reduction interventions. (3rd December 2012) - Ferri, Marica; Bo, Alessandra
Abstract : Best practice is the best application of available evidence to current activities in the drugs field. In 2008, the European Monitoring Centre for Drugs and Drug Addiction (EMCDDA) set off the creation of a web-based tool which bridges together scientific evidence and current practices in the drug addiction field. The aim is to disseminate evidence-based interventions and promote sharing of best practice amongst the European countries. The synthesis of the evidence is based on sound procedures, implemented according to the methods of the Cochrane collaboration (the Drugs and Alcohol Group) and the Grade working group. As of October 2012, the portal is composed of four modules on the effectiveness of demand reduction interventions, a collection of European projects on prevention, treatment, harm reduction and social reintegration and an inventory of European Guidelines and Standards including a bank of instruments to evaluate interventions (http://www.emcdda.europa.eu/best-practice ). The summaries of evidence are presented in a user-friendly format and provide plain language information on the interpretation of the measures of effect supporting the evidence, but do not provide specific recommendations. The main future challenge of EMCDDA's best practice promotion is to enhance the communication of evidence to better inform the decision making processes both at national and European level.